Self-Determination Theory and Accountant Employees’ Psychological Wellbeing: The Roles of Positive Affectivity and Psychological Safety - Lin, Philip Teng; Vu, Thinh Truong; Nguyen, Van Phuong; Wu, Qi (Frontiers in Psychology, 2022)
This study investigates the influence of self-determination motivations on accountant employees’ psychological wellbeing with the mediating role of positive affectivity and the moderating role of psychological safety. Multivariate analysis and structural equation modeling are used to analyze a three-way time-lagged sample data of 391 accountant employees. Results indicate that positive affectivity positively mediates the relationship between extrinsic motivation and psychological wellbeing and between intrinsic motivation and psychological wellbeing. Furthermore, psychological safety positively moderates the relationship between extrinsic motivation and positive affectivity and between intrinsic motivation and positive affectivity. In addition, psychological safety also positively moderates the relationship between positive affectivity and psychological wellbeing. The findings of this study provide implications for researchers and business managers in managing and enhancing accountant employees’ psychological wellbeing.